Management of mountain watersheds - Krecek, Josef (Springer Netherlands, 2012)
The book aims to address the interdisciplinary targets of watershed management in mountain regions based on the current knowledge of the subject. The focus of the book is particularly on monitoring, research, and modelling the interactions between the climate, water cycle, and aquatic ecosystem. The issues of watershed management in mountain regions in different parts of Europe, Africa, America and Asia have been the central theme of the book, which is basically divided into five sections: Hydrological processes and stream habitat in mountain catchments; Man's impacts on mountain environment; Climate change considerations; Monitoring and mitigation of disasters; and Sustainable watershed management. The articles have been peer reviewed and the interdisciplinary team of authors includes experts from the specialised areas of geography, hydrology, chemistry, biology, forestry, ecology, economy and sociology. The practical applications and management strategies mentioned in the book, deal with the multi-resource concept, based on the compromise between the development, conservation/ protection of the nature. Finally, the socio-economic and cultural aspects, and ecosystem prevalent in a mountain catchment are discussed in detail.